Effect of cold stress on growth, physiological responses, blood metabolites and hormonal profile of native Malpura lambs under hot semi-arid tropics of India - MAURYA, V P; SEJIAN, V; NAQVI, S M K (The Indian Journal of Animal Sciences, 2013)
The study was conducted to determine the effect of cold stress on growth, physiological responses, blood metabolitesand hormones. Growing native Malpura lambs (18), 45 to 60 days of age, 14.8 kg body-weight, were used in this study.The lambs were randomly divided into 2 groups as group 1 (9) and group 2 (9). The experiment was conducted frommid-January to mid-February when the environmental temperature was at the lowest. The lambs of G1 were kept under the asbestos shed open from the sides while the lambs of G2 were provided protection against the cold weather. Thebody weight (kg), physiological responses i.e. respiration rate (RR, breath/min), pulse rate (PR, beat/min) and rectaltemperature (RT,Â°C) were recorded at fortnightly interval. The blood samples were also collected at fortnightly intervaland analyzed for packed cell volume (PCV,%), haemoglobin (Hb, g/dl) and glucose (mg/dl). Besides the T3 (nmol/l), T4 (nmol/l) and cortisol (nmol/l) were also estimated. The lambs of G1 had higher RR, PR and RT than the G2 lambs. Asignificant increase in the PCV, Hb and glucose was observed in G1 lambs as compared to G2. The ADG was significantlyhigher in G2 lambs as compared to G1 lambs.